Applying the elements of visual communication in making a webtoon series that depicts the lived experiences of bisexual men - Borja, Ethnic Serc D.; Sanchez, Samuelle Marionne C. (2023)
By employing the fundamentals of visual communication design, this production research examined the webtoon as a visual medium for depicting the lived experiences of bisexual men. Five bisexual men identifying as such were invited to participate in the study and shared their narratives and lived experiences. All of them are Davao City residents aged 18 to 30. These narratives serve as the basis for the webcomic's plot and were structured to create a coherent narrative. Using Campbell's Hero's Journey (1990), the fundamental principles of a plot that focuses on overcoming an obstacle, in this case, the ownership of gender identity in a heteronormative society, were applied to generate a story. After conceptualizing the plot, the researcher designs the character that complements it most effectively by incorporating the four elements of the narrative statement: the symbol of character, the symbol of desire, the symbol of action, and the symbol of outcome. The creation of the webtoon series is governed by Mayer's Cognitive Theory of Multimedia Learning, which employs 12 instructional principles to reduce cognitive load. The application of the fundamentals of design such as lines, shapes, and colors helped elicit messages to the target audience. These stages led to the creation of the webtoon series that depicts the lived experiences of bisexual men and served as a platform to represent bisexuality as a gender identity and at the same time contributed to the LGBTQIA++ realities, thus the webtoon series became a media artifact of genuine representations of bisexual identities and experiences.
Thesis (BA Communication and Media Arts) -- University of the Philippines Mindanao, 2023